2010
DOI: 10.1097/pas.0b013e3181f8be17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Her-2 in Carcinomas of the Esophagus

Abstract: The human epidermal growth factor receptor-2 gene (HER-2) encodes for a membrane-bound tyrosine kinase (Her-2), which is overexpressed in various human cancers. Her-2-targeted therapy has recently been shown to be beneficial for patients with advanced gastric cancer. Her-2 protein expression was investigated in 341 esophageal carcinomas [152 squamous cell carcinomas (SCC), 189 adenocarcinomas (AC)], 39 cases of Barrett mucosa, and 11 cases of squamous cell dysplasia. HER-2 gene amplification was assessed by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 1 publication
4
42
3
Order By: Relevance
“…4,16,17,32 Nevertheless, due to the detection of novel mechanisms and development of targeted therapies, small and smaller subgroups of cancer patients are identified, which may benefit from a targeted therapy. Therefore, for example, in non-small cell lung cancer, the rates of patients with tumors showing ALK translocations or EGFR mutations, which represent targets for novel therapies, are also below 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16,17,32 Nevertheless, due to the detection of novel mechanisms and development of targeted therapies, small and smaller subgroups of cancer patients are identified, which may benefit from a targeted therapy. Therefore, for example, in non-small cell lung cancer, the rates of patients with tumors showing ALK translocations or EGFR mutations, which represent targets for novel therapies, are also below 10%.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The role of HER has also been studied in several other cancers, including bladder cancer, endometrial cancer, gastroesophageal cancer, ovarian cancer, lung cancer, osteosarcoma, and prostate cancer. [9][10][11][12][13][14][15][16][17] Recently, the monoclonal HER2-blocking antibody trastuzumab has also been FDA approved for the treatment of HER2 overexpressing advanced stage gastroesophageal cancer, in addition to breast cancer. 18 Despite combination of surgical treatment with adjuvant chemotherapy, the outcome of pancreatic ductal adenocarcinoma (PDAC) is one of the worst of all malignancies as it is the fourth leading cause of death from cancer in the United States.…”
mentioning
confidence: 99%
“…Siewert type III tumors involve intestinal metaplasia less often, and there is a higher proportion of the undifferentiated type. Siewert type II tumors fall between types I and III in most characteristics, but the proportion of human epidermal growth factor receptor 2 positivity in type II tumors is higher than in types I and III [8]. Although there is almost an even distribution among these three types in Western countries, there are very few Siewert type I patients in Eastern countries [7,9,10].…”
Section: Characteristics Of Egj Tumorsmentioning
confidence: 99%
“…In addition, HER2 is a therapeutic target in several types of cancer. Previous studies have observed that the oncogene HER2/neu was overexpressed in 2.0-19.1% cases of ESCC (6)(7)(8)(9)(10)(11)(12)(13), and increased protein expression levels of HER2 have been previously observed in EC (14,15) and ESCC (6,7). However, the role of HER2 in ESCC remains controversial (6,7,9,10,12,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 90%